Animal sacrifice in the ancient Greek world - Hitch, Sarah ca. 20./21. Jh.; Rutherford, Ian 1959- (Cambridge Cambridge University Press, 2017)
This volume brings together studies on Greek animal sacrifice by foremost experts in Greek language, literature and material culture. Readers will benefit from the synthesis of new evidence and approaches with a re-evaluation of twentieth-century theories on sacrifice. The chapters range across the whole of antiquity and go beyond the Greek world to consider possible influences in Hittite Anatolia and Egypt, while an introduction to the burgeoning science of osteo-archaeology is provided. The twentieth-century emphasis on sacrifice as part of the Classical Greek polis system is challenged through consideration of various ancient perspectives on sacrifice as distinct from specific political or even Greek contexts. Many previously unexplored topics are covered, particularly the type of animals sacrificed and the spectrum of sacrificial ritual, from libations to lasting memorials of the ritual in art.
Introduction / Ian Rutherford and Sarah Hitch -- Part I. Victims -- Bare Bones : Zooarchaeology and Greek Sacrifice / Gunnel Ekroth -- Venison for Artemis? : The Problem of Deer Sacrifice / Jennifer Larson -- Don't kill the goose that lays the golden egg? : Some thoughts on bird sacrifices in ancient Greece / Alexandra Villing -- Part II. Procedure -- Reflections on Sacrifice and Purification in the Greek World / Stella Georgoudi -- "Polis Religion" and Sacrificial Regulation / Fred Naiden -- Meaty Perks : Epichoric and Topological Trends / Mathieu Carbon -- Part III. Representation -- Sacrifice and the Homeric Hymn to Hermes 112-41 / Oliver Thomas -- Visualising Veneration : Images of Animal Sacrifice on Greek Votive Reliefs / Anja Klockner -- Sacrifice in Drama : The Flow of Liquids / Richard Seaford -- Part IV. Margins -- Animal Sacrifice in Hittite Anatolia / Alice Mouton -- The Reception of Egyptian Animal Sacrifice in Greek Writers / Ian Rutherford -- A Quiet Slaughter? : Julian and the Etiquette of Public Sacrifice / Sergio Knipe
Title from publisher's bibliographic system (viewed on 30 Aug 2017)
Keywords: Animal sacrifice -- Greece -- History; Ritual -- Greece -- History; Animal remains (Archaeology) -- Greece; Excavations (archaeology) -- Greece; Social archaeology -- Greece; Excavations (archaeology) -- Greece; Social archaeology -- Greece; Animal sacrifice -- Greece -- History; Animal remains (Archaeology) -- Greece; Ritual -- Greece -- History; Animal sacrifice ; Greece ; History; Ritual ; Greece ; History; Animal remains (Archaeology) ; Greece; Excavations (Archaeology) ; Greece; Social archaeology ; Greece; Greece ; Religious life and customs; Greece ; Antiquities; Greece -- Religious life and customs; Greece -- Antiquities; Greece -- Religious life and customs; Greece -- Antiquities; Aufsatzsammlung